PENGHORMATAN PRINSIP-PRINSIP KEMANUSIAAN TERHADAP TAWANAN PERANG DALAM KONFLIK BERSENJATA MENURUT KONVENSI JENEWA III TAHUN 1949 (Studi Kasus Penyiksaan Tawanan Perang AS Di Penjara Guantanamo) - Danial Danial (Jurnal Idea Hukum, 2015)
Humanitarian principle aims to protect and ensure respect for the human. This research uses a normative, and the research also applies a descriptive-analytical approach to examine and analyse the research questions of the thesis. In doing so, this research uses a secondary data, These legal materials are subsequently analysed using a qualitative juridical approach.The results showed that the First, the concept of legal protection of prisoners of war under the Geneva Convention III 1949 indicates that the combatants who have the status of 'hors de combat' must be protected and respected in all circumstances. Tribute in the form of an obligation not to commit acts harmful, do not aggravate the situation, and do not kill people who are protected. Penahanpun state obligation to prevent harm and damage; Second, implementation of the Geneva Convention III 1949 against US prisoners of war in Guantanamo is not optimal. This happens because of differences in the interpretation of the Articles in International Humanitarian Law so as to cause the indication practices inhumane treatment, no legal protection, not considered welfare and not related to the outside world at Guantanamo will be undertaken by the US military guards.Keywords: Respect, Humanity, Prisoner of War, Armed Conflict, Guantanamo